Some Dynamical Properties of Rössler System - Jassim, Hassan Kamil (University of Thi-Qar Journal, 2019)
This paper characterizes some dynamical properties of Rössler system. We consider the stability of equlibria points of Rössler system and also stability of system when . We investigate existence of transcritical bifurcation and Hopf bifurcation in Rössler system. Compute the largest Lyaponuv exponent at the critical points in the special case